Collaborative Networks in Chronic Disease Prevention: What Factors Inhibit Partnering for Funding?. Issue 2 (25th January 2021) - Hopkins, Liza; Chamberlain, Daniel; Held, Fabian; Riley, Therese; Wang, Jean Zhou Jing; Conte, Kathleen
ABSTRACT: Inter-organisational partnering is seen as an effective mechanism for improving the delivery of chronic disease interventions in communities. Yet even in communities where organisations across multiple sectors are well connected and collaborative in other ways, when it comes to partnering for joint-funding, multiple barriers inhibit the establishment of formal partnerships. To understand why this is so, we examined quantitative and qualitative data from organisations in an Australian community and compared the findings with a review of the published literature in this area. We found that even organisations which are well connected through informal network arrangements face pressure from funding bodies to form more formalised inter-organisational partnerships. Community based organisations also recognise that partnerships are desirable mechanisms for service improvement; however, barriers to joint-funding partnerships exist which include restrictions imposed by funding bodies on the way grants are designed, implemented, and administered. Additional barriers at the community level include organisational capacity for partnership work, intra-organisational restrictions and timing issues. Policy makers must recognise and address the barriers to partnerships which exist within funding structures and at the community level in order to increase partnering opportunities to improve service delivery.